Effect of four insecticides and Beauveria bassiana on Prorops nasuta (Hymenoptera: Bethylidae) parasitoid of the coffee berry borer - MEJÍA-M., JHON WILSON; BUSTILLO-P., ALEX E.; OROZCO-H., JAIME; CHÁVES-C., BERNARDO (Revista Colombiana de Entomología, 2000)
The integrated coffee berry borer management includes the use of both biological and chemical components when required. This IPM approach requires that the different control systems used must be compatible. This study evaluated under field conditions the effect of chlorpyrifos, endosulfan, fenitrothion, pirimiphos-methyl and Beauveria bassiana on adults of the parasitoid, Prorops nasuta to determine the time-lapse to use these methods of control without causing incompatibility. Two experiments were conducted in two coffee plots of Colombian coffee variety. The first consisted of spraying the insecticides and then the release of P. nasuta after 1, 7, 14, 22, and 29 days. In the second experiment, P. nasuta was released first and then the insecticides were sprayed at 1, 7. 15, 21, and 29 days. A complete randomized design with factorial array: 5 (insecticides) x 5 (release/spray time) x 4 (replications) was implemented. The experimental unit was one branch/tree with 40 berries, which were kept with the aid of a sleeve nylon entomological cage and was infested with adults of coffee berry borer. Thirty-three days after infestation the spray of insecticides or release of parasitoids were made. Results showed that all the insecticides caused mortality to P. nasuta and that mortality decreased as the time between control methods was greater. Results showed that when insecticides are sprayed ·first, the mínimum time elapsed to release parasitoids should be 22 days; but when the parasitoids are released first it is advisable to wait 9 days before spraying B. bassiana and 20 days to spray the insecticides. Endosulfan was showed not to be selective against P. nasuta.